2017
DOI: 10.18256/2237-7956/raimed.v6n2p162-172
|View full text |Cite
|
Sign up to set email alerts
|

Pricing Strategy in Multi-Channel Retailing and Fairness Perception: an Examination of Boundary Conditions

Abstract: This article aims to examine the boundary conditions that influence the relationship between pricing strategy in multi-channel retailing and fairness perception, since past research has found controversial results concerning this subject. In experiments 1 and 2, we show that differential pricing is perceived as fairer for products in comparison to services. In experiment 3, we show that when the price difference is justified by an explanation based on costs, it is perceived as fairer than an explanation based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…One of the directions of reducing negative consequences is an attempt to provide an explanation for the observed differences in prices. Becker et al (2016) suggest that, if only possible, an explanation for different prices based on channels costs should be provided. Cost-based communications as well as value-based communications are recommended by Fassnacht and Unterhuber (2016).…”
Section: Discussionmentioning
confidence: 99%
“…One of the directions of reducing negative consequences is an attempt to provide an explanation for the observed differences in prices. Becker et al (2016) suggest that, if only possible, an explanation for different prices based on channels costs should be provided. Cost-based communications as well as value-based communications are recommended by Fassnacht and Unterhuber (2016).…”
Section: Discussionmentioning
confidence: 99%
“…Martín-Ruiz and Rondán-Cataluña (2008) found that, while perceptions of price fairness and unfairness across goods and services share similar antecedents, consumers of services react more strongly than consumers of goods to perceptions of unfair prices. Becker et al (2017) showed that differential pricing for identical goods/services across different channels (e.g., online or offline) is perceived to be fairer for goods as compared to services. Both Martín-Ruiz and Rondán-Cataluña ( 2008) and Becker et al (2017) attribute their findings to the intangibility of services, which increases consumers' perceived vulnerability to unfair prices (Martín-Ruiz and Rondán-Cataluña, 2008) and makes price differences across channels harder to justify (Becker et al, 2017).…”
Section: Price Fairness and Emotional Antecedentsmentioning
confidence: 99%
“…Becker et al (2017) showed that differential pricing for identical goods/services across different channels (e.g., online or offline) is perceived to be fairer for goods as compared to services. Both Martín-Ruiz and Rondán-Cataluña ( 2008) and Becker et al (2017) attribute their findings to the intangibility of services, which increases consumers' perceived vulnerability to unfair prices (Martín-Ruiz and Rondán-Cataluña, 2008) and makes price differences across channels harder to justify (Becker et al, 2017).…”
Section: Price Fairness and Emotional Antecedentsmentioning
confidence: 99%
See 2 more Smart Citations